Decline in unmet needs for cataract surgery among the ageing population in India: findings from LASI, wave-1 - Das, Sasmita; Sinha, Abhinav; Kanungo, Srikanta; Pati, Sanghamitra (Frontiers in Health Services, 2024)
Introduction Cataracts are the leading cause of blindness among older people, but they can be treated with corrective surgery. India boasts the oldest blindness control programme in the world. We aimed to assess the prevalence of cataract surgery, and we compared the determinants of undergoing cataract surgery and identified the unmet needs for cataract surgery among older adults in India. Methods We included 52,380 individuals aged ≥50 years from the Longitudinal Ageing Study in India, wave-1. The primary outcome measures of our study were the prevalence of cataract surgery and the unmet need for cataract surgery. Multivariate analysis was executed to investigate the association between socio-demographic variables and outcomes, expressing the results as adjusted odds ratios with 95% confidence intervals (CIs). Results The overall prevalence of cataracts was 14.85%. The coverage of cataract surgery was 76.95%, with 23% having unmet needs for cataract surgery. Notably, cataract surgery coverage was higher at 78.30% (95% CI: 76.88–79.48) among participants aged 66–80 years, while the percentage of those who did not undergo cataract surgery was higher at 24.62% (95% CI: 23.09–26.20) among participants aged 50–60 years. The most deprived group had a higher odds ratio [adjusted odds ratio: 1.20 (95% CI: 1.00–1.44)] (p < 0.05) of having unmet needs for cataract surgery. Conclusions There is a considerable burden of age-related cataracts in India. While the coverage of cataract surgery is high, the unmet need for cataract surgery cannot be overlooked. The existing blindness control programme has contributed significantly to increasing the coverage of cataract surgery, but it still needs to be strengthened, especially to reach the most deprived sections of society.